Effects of changes in living environment on physical health: A prospective cohort study of movers and non-movers in Germany - Benjamin Aretz; Gabriele Doblhammer; Fanny Janssen (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Longitudinal studies on associations between changes in living environment and health are few and focus on movers. Next to causal effects, differences in health between living environments can, however, result due to residential mobility. The present study explored changes in living environment related to (changes in) physical health among movers and non-movers. Causality was reinforced by a novel study design. We obtained longitudinal data on both living environment and physical health covering 4,373 participants with 12,403 health observations aged 50+ from the Socio-Economic Panel (SOEP) between 1999 and 2014. Changing and stable perceived living environmental characteristics from four domains (infrastructure, environmental pollution, housing conditions, contacts to neighbours) were included at household level. Gender-specific linear regressions and generalised estimating equations were performed to predict the Physical Component Summary (PCS) at baseline and changes in PCS over time. We found that worsening of environmental pollution (men: -2.32, p = 0.001; women: -1.68, p = 0.013) and housing conditions were associated with lower PCS at baseline. Improved infrastructure was related to lower women's PCS at baseline (-1.94; p = 0.004) but a positive PCS development (0.62, p = 0.095) thereafter among female and especially among female non-movers (0.812, p = 0.042). Men who experienced stable worst (-0.57, p = 0.021) or worsened environmental pollution (-0.81, p = 0.036) indicated a negative developing PCS. These results were particularly strong among non-movers. We showed that changes in infrastructure and environmental pollution were associated with health developments. Due to our methodological approach - imposing a strict time order between cause and outcome while controlling for time-varying individual characteristics - it appears that these associations are indeed causal.
Keywords: 330; changes in living environment; physical component summary; changes in physical health; movers and non-movers; generalized estimating equations; causal inference